Technical Aspects of in vivo Small Animal CMR Imaging - Li, Hao; Abaei, Alireza; Metze, Patrick; Just, Steffen; Lu, Qinghua; Rasche, Volker (Frontiers in Physics, 2020)
Magnetic resonance imaging (MRI) has become an accurate and versatile imaging modality to visualize the cardiovascular system in normal or abnormal conditions. In preclinical research, small rodent animal models of human cardiovascular disease are frequently used to investigate the basic underlying mechanism of normal and abnormal cardiac function and for monitoring the disease progression under therapy. Technological improvements in MRI have been extended to small animals such non-invasively providing insights into cardiac morphology, function, perfusion and pathophysiology in various cardiac disease. This article reviews the basic technical approaches to in vivo small animal magnetic resonance imaging and its variants for the most promising applications.